2022
DOI: 10.1101/2022.06.13.495989
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissociating the contributions of sensorimotor striatum to automatic and visually-guided motor sequences

Abstract: The ability to sequence discrete movements in new ways enables rich and adaptive behavior. Such flexibility can be computationally costly and result in halting performances. Practicing the same motor sequence repeatedly, however, can render its execution precise, fast, and effortless, i.e., ‘automatic’. The basal ganglia are thought to underlie both flexible and automatic motor sequences, yet how their contributions differ across these modes is unclear. We parse this in rats trained to perform the same motor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(36 citation statements)
references
References 170 publications
(545 reference statements)
2
33
1
Order By: Relevance
“…While we did not find evidence for the DLS controlling species-typical behaviors, our analysis of motor skills suggested, in concert with earlier studies 36,38,39,41 , that it is essential for shaping learned movement kinematics. Densely innervated by dopaminergic neurons signaling reward prediction error 100 , sensorimotor striatum could learn to map state input from cortex and thalamus to activity patterns that help shape future actions in adaptive and task-specific ways 2,101 .…”
Section: The Role Of Bg In Learningcontrasting
confidence: 54%
See 3 more Smart Citations
“…While we did not find evidence for the DLS controlling species-typical behaviors, our analysis of motor skills suggested, in concert with earlier studies 36,38,39,41 , that it is essential for shaping learned movement kinematics. Densely innervated by dopaminergic neurons signaling reward prediction error 100 , sensorimotor striatum could learn to map state input from cortex and thalamus to activity patterns that help shape future actions in adaptive and task-specific ways 2,101 .…”
Section: The Role Of Bg In Learningcontrasting
confidence: 54%
“…Our study considers a fundamental distinction in how the BG contribute to movement, specifically asking whether this region is essential for general control or specialized for acquiring and controlling learned motor skills (Fig 1). Using high-resolution 3D kinematic tracking in freely behaving rats, we showed that lesions of the sensorimotor striatum did not affect the expression ( 36,41 ). To probe the neurophysiological correlates of this difference, we recorded from the same cells in sensorimotor striatum during both learned and species-typical behaviors.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This allows us to probe motor cortex's contributions to higherlevel functions without the ambiguity of it being necessary for basic movement control. Second, rats can master fairly complex discrete sequence production tasks 29 akin to those frequently used in human and non-human primate studies of motor sequence learning and execution 30,31 . The rich structure of such tasks allows us to probe motor cortex's contributions to the flexible sequencing of motor elements.…”
Section: Introductionmentioning
confidence: 99%